Martin Luther King, Jr., and the theology of resistance - Burrow, Rufus, 1951- (McFarland & Company, Inc., Publishers, 2015)
"It has been nearly fifty years since Martin Luther King, Jr., was assassinated. Appraisals of King's contributions began almost immediately and continues to this day. The author explores an astonishing number of King's chief ideas and social-ethical practice. Burrows' essays reveal the strengths and limitations in King's theological socio-ethical project"--